2016
DOI: 10.1007/s11010-016-2738-6
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing canonical Wnt signaling pathway by recombinant human sFRP4 purified from E. coli and its implications in cancer therapy

Abstract: The Wnt signaling pathway plays a predominant role in aberrant proliferation in myriad of cancers. In non-cancerous cells, Wnts are blocked by the secreted frizzled-related proteins (sFRPs) that are generally downregulated in cancer cells. We have purified and characterized bacterially expressed glutathione S-transferase-tagged SFRP4 from a novel clone generated from human cell origin. Cervical cancer (HeLa) and lung cancer (A549) cells, in which Wnt and associated genes were found to be expressed, were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…It can inhibit the activation of the Wnt signaling pathway by competitively binding with receptors related to the Wnt signaling pathway. The present data indicated that the expression levels of SFRP4 were decreased at both the mRNA and protein levels in FLS, which was in accordance with findings from other relevant research studies (77,78). Notably, after lncRNAS56464.1 interference, the expression of SFRP4 was significantly increased.…”
Section: Discussionsupporting
confidence: 92%
“…It can inhibit the activation of the Wnt signaling pathway by competitively binding with receptors related to the Wnt signaling pathway. The present data indicated that the expression levels of SFRP4 were decreased at both the mRNA and protein levels in FLS, which was in accordance with findings from other relevant research studies (77,78). Notably, after lncRNAS56464.1 interference, the expression of SFRP4 was significantly increased.…”
Section: Discussionsupporting
confidence: 92%
“…Activation of the canonical WNT pathway has been described to affect proliferation and migration of various non-rhabdomyomatous tumor cells through induction of the targets such as the pro-proliferative protein MYC and the pro-proliferative and anti-apoptotic IAP-protein BIRC5 (survivin) (29, 30). We here tested the effects of FH535, XAV939, β-catenin siRNA, and WNT3A treatment on proliferation and expression of the mentioned β-catenin target genes in the above mentioned RMS cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt/β-catenin signaling has been demonstrated to serve an important role in regulating tumor initiation and progression in various malignant tumor types, including lung cancer and HCC ( 27 , 28 ). Furthermore, Wnt signaling may regulate genes that are involved in cell-cycle regulation and cell apoptosis, including Cyclin and Bcl-2 ( 29 ).…”
Section: Discussionmentioning
confidence: 99%